Forståelse av åndelighet og åndelig omsorg for gamle mennesker – en hermeneutisk studie - Rykkje, Linda (Nordisk tidsskrift for helseforskning, 2016)
Understanding spirituality and spiritual care for older people – a hermeneutical study In old age, spirituality and existential issues may become salient. The study aim is an understanding of older peoples’ perception of spirituality and spiritual care in a Norwegian context. Gadamer hermeneutics is the guiding methodology. 30 interviews were conducted with 17 participants between 74-96 years, six self-reliant, five with homecare, and six nursing home residents. The findings present understanding of spirituality, soul and spirit, the meaningful in life, inner peace, care from family in old age, and spiritual care. The study discusses spirituality as a force that contributes to wholeness and health, especially by the experience of “inner calm and peace”. That which may contribute to inner peace is love for fellow human beings and being with others, religion and nature, together with meaningful activities and feeling “alive”. Spiritual care involves “to care about” the whole person through compassionate care, presence, listening, touch and facilitating socializing and activities.